Results of mitral valve reconstruction using substitute extracellular matrixCentral MessagePerspective - Maria Arbona, MD, MEBCT; Tirone E. David, MD; Carolyn M. David, BN; Vivek Rao, MD, PhD (JTCVS Techniques)
Background: During the ongoing search for an ideal patch material for reconstructive heart surgery, several versions of extracellular matrix (ECM) have been used. However, long-term performance in different cardiac positions is unknown. Methods: We performed a retrospective review of outcomes after mitral valve surgery using ECM in 29 patients from 2011 to 2014. Clinical and echocardiographic follow-up was reviewed (mean time, 6.3 ± 2.8 years). Results: ECM was used to reconstruct the posterior mitral annulus in 69% and to repair the mitral leaflet in 65% of the patients. The most prevalent etiology was dystrophic calcification of the annulus (80%) versus endocarditis for leaflet repair (60%). Fifty-five percent of the patients who required annular reconstruction received a mitral valve replacement (MVR). There were 2 perioperative deaths (7%). Long-term data were analyzed according to surgical technique; namely, isolated leaflet repair compared with annular reconstruction with or without MVR. There were 3 late deaths (1 per group). Overall survival was 83% at 7 years. Ninety percent of cases with mitral valve repair with or without annular reconstruction were free from more than mild mitral regurgitation, compared with 45% in the MVR and annular reconstruction group. The mechanism of failure was patch degeneration creating a severe paravalvular leak due to prosthesis dehiscence. Conclusions: ECM used to repair the mitral valve leaflets with or without annular reconstruction offers acceptable results. However, caution should be taken with the use of ECM adjacent to prosthetic valve material because of a high rate of failure associated with patch degeneration.